Online Interactive Multimedia Oriented to HOTS through E-Learning on Physics Material about Electrical Circuit - Sri Wahyu Widyaningsih; Irfan Yusuf; Zuhdan Kun Prasetyo; Edi Istiyono (Jurnal Pendidikan Indonesia, 2020)
This article explains the development of interactive multimedia which is designed using e-learning. The development technique uses ADDIE model which consists of some stages namely Analyze, Design, Development, Implementation, and Evaluation. The trial subjects in this study were 13 students of Physics Education Department in Universitas Papua who programed basic physics courses in the even semester of 2018-2019. Interactive multimedia validity was obtained based on an assessment sheet filled by 7 validators consisting of material expert validators, media experts and practitioners. Meanwhile, the effectivity and practicality of interactive multimedia was obtained based on the students’ responses after learning. The instrument used in this study was the validation sheet filled out by the validators and questionnaire about students’ responses after learning. The technique used to analyze the results of the validator's assessment was V Aiken while the questionnaire analysis used Rasch model. The results showed that the developed learning media were in the valid category for each aspect of the assessment, namely layout, navigation, functions, and pedagogy aspects. Moreover, students’ responses towards interactive multimedia used were also effective and practical in every aspect of assessment. Students gave good responses towards HOTS abilities that could be developed during learning, including the ability to analyze, evaluate, and create. Therefore, online interactive multimedia oriented to HOTS through e-learning can be applied in physics lesson.